The geographic reach of community-based organizations in addressing HIV-related stigma in the Deep South. Issue 1 (2nd January 2022) - Belden, Micha; Reif, Susan; Cooper, Haley; Shilling, Sara; Mouhanna, Farah; Hipp, Palmer; Siegler, Aaron
ABSTRACT: Community-based organizations (CBOs) have been instrumental in addressing the needs of people living with HIV, however, little is known about their efforts to address HIV-related stigma through stigma reduction efforts. This study examined practices of CBOs related to mitigating HIV-related stigma in nine Deep South states. CBOs were surveyed as part of a larger study through the Gilead COMPASS Initiative. The CBO survey asked CBO leadership about stigma in their communities and services available to address this stigma. Survey respondents ( n  = 207) indicated that HIV-related stigma was perceived as a substantial barrier to both HIV care and CBO services. Although just over two-thirds of survey participants reported that there were group-level programs to address HIV-related stigma, 73% reported that there were not enough interventions to meet the need in their community. Further, 68% reported a lack of individual-level stigma reduction interventions. A majority reported a lack of public media campaigns to address stigma and a lack of training available to assist CBOs to address stigma. In addition, services to address stigma were reportedly less available in rural areas compared to their urban counterparts. Study findings indicate a need to identify, implement, and scale-up effective interventions to reduce HIV stigma in the US Deep South.